The Perversity of Preferences : The Generalized System of Preferences and Developing Country Trade Policies, 1976-2000 - Ozden, Caglar (World Bank, Washington, DC, 2014)
Industrial countries maintain special tariff preferences, namely the Generalized System of Preferences (GSP), for imports from developing countries. Critics have highlighted the underachieving nature of such preferences, but developing countries continue to place the GSP at the heart of their agenda in multilateral negotiations. What effect do such preferences have on a recipient's own trade policies? The authors develop and test a simple theoretical model of a small country's trade policy choice, using a dataset of 154 developing countries from 1976 through 2000. They find that countries removed from the GSP adopt more liberal trade policies than those remaining eligible. The results, corrected for endogeneity and robust to numerous alternative measures of trade policy, suggest that developing countries may be best served by full integration into the reciprocity-based world trade regime rather than continued GSP-style special preferences.